Science, religion and deep time - Gustafson, Lowell S.; Rodrigue, Barry H.; Blanks, David R. 1961- (Routledge, Taylor & Francis Group, 2022)
"This book examines the meaning of religion within the scientific, evidence-based history of our known past since the big bang. While our current major religions are only centuries or millennia old, the volume discusses the origins and development of human religious practice and belief over our species' existence of 300,000 years. The volume also connects the scientific approach to natural and social history with ancient truths of our religious ancestors using new lines of inquiry, new technologies, new modes of expression, and new concepts. It brings together insights of natural scientists, social scientists, philosophers, writers, and theologians discuss to the narratives of the universe. The essays discuss that to apprehend religion scientifically, or to interpret and explain science theologically, the subject must be examined through a variety of disciplinary lenses simultaneously and raise several theoretical, philosophical, and moral problems. A singular investigation into the meaning of religion in the context of the 13.8 billion-year history of our universe, this book will be indispensable for scholars and students of religious studies, big history, sociology and social anthropology, philosophy, and science and technology studies"--
Keywords: Religion; Weltgeschichte; Wissenschaft; Religion and science; Religion and civilization; Science and civilization; History / Philosophy; Cosmology; Religion and Science; Religion et sciences; Religion et civilisation; Sciences et civilisation; Cosmologie; cosmology; Aufsatzsammlung